Anaerobic electrogenic oxidation of toluene in a continuous-flow bioelectrochemical reactor: process performance, microbial community analysis, and biodegradation pathways. Issue 12 (7th November 2018) - Palma, Enza; Daghio, Matteo; Espinoza Tofalos, Anna; Franzetti, Andrea; Cruz Viggi, Carolina; Fazi, Stefano; Petrangeli Papini, Marco; Aulenta, Federico
Abstract : High-rate anaerobic oxidation of toluene was achieved in a continuous-flow bioelectrochemical system. Abstract : Microbial electrochemical systems (MES) represent an innovative reagent-free technology for in situ remediation of groundwater contaminated by petroleum hydrocarbons. Here we describe the long-term (>160 days) anaerobic treatment of synthetic groundwater containing toluene (25 mg L −1 ) in a novel laboratory-scale, continuous-flow bioelectrochemical reactor, termed the "bioelectric well". Under optimal operating conditions ( i.e., anode potential potentiostatically controlled at +0.2 V vs. SHE and recycle flow-rate set at 75 mL min −1 ), the observed electrogenic toluene oxidation rate was 67.2 ± 5.7 mg L d −1, a value which is among the highest reported in the literature for laboratory-scale anaerobic treatment systems. Correspondingly, electric current was 5.1 ± 0.1 mA and the Coulombic efficiency ( i.e., the yield of toluene conversion into electric current) was 79 ± 7%. Electrogenic toluene oxidation was most likely catalyzed by Geobacter species, which were found to dominate the surface of the graphite anode. The combined application of GC-MS (for detection and identification of metabolites) and qPCR (for quantification of functional genes) revealed that toluene degradation was initiated by fumarate addition, an activation pathway that is widely distributed among anaerobic hydrocarbon-degrading microorganisms. Collectively, the results of this study indicate that the bioelectric well holds remarkable potential for in situ treatment of groundwater contaminated by petroleum hydrocarbons.